Educational Leadership in AI Integration: Enhancing Teacher Literacy and Performance Management - AL KHAFAJY, RANIA HAMEED HASSAN (2025)
This study examines the essential function of educational leadership in the successful incorporation of artificial intelligence (AI) within schools in the UAE, aiming to improve teacher literacy, professional growth, and performance management. By conducting an in-depth analysis of educators' perceptions, experiences, and requirements, the research investigates how strategic leadership approaches affect teachers' capabilities and readiness to utilise AI tools in their instruction. The findings indicate that visionary leadership, well-structured support systems, and focused, ongoing professional development play a crucial role in enhancing teachers' skills and confidence in AI technologies. Furthermore, the ethical and transparent application of AI analytics to deliver personalised and constructive feedback is identified as a vital element in elevating instructional quality and educational outcomes. This research offers a distinctive contribution to the understanding of AI's educational ramifications within the UAE, highlighting the importance of continuous professional development, ethical AI practices, and inclusive strategies as fundamental aspects for effective AI integration. Ultimately, the study equips educational leaders and policymakers with valuable strategies and insights to effectively navigate the intricate challenges of ethical and efficient AI implementation in educational settings. Keywords: Educational Leadership, Artificial Intelligence, Teacher Literacy, Professional Development, Performance Management, AI Analytics, Ethical AI Integration, Instructional Quality, UAE Schools